ANOTHER TWIST... THE ANSWER TO A. POLONNIKOV - A. S. Robotova (Высшее образование в России, 2017)
The paper is constructed as a polemical reflection, as a response to A.A. Polonnikov's article about the complex relationships between the language system ofpedagogical sciences and its reflection in the image of pedagogical reality.